Abuse of Authority by Public Officials in the Election Process - Dwi Novitasari; Firmansyah Firmansyah; Nety Hermawati (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2026)
This study discusses the abuse of authority by public officials in the Regional Head Election (Pilkada) with a study on Court Decision Number 191/Pid.Sus/2024/PN. With. The background of the problem is the practice of politicizing state positions, government programs, and facilities that damage the integrity of democracy and violate the principle of apparatus neutrality. The main problem studied is how the form of abuse of authority is carried out by incumbent officials and how the judge considers the fulfillment of the elements of election crimes. This study uses normative legal methods with a legislative and case approach, analyzing Law No. 30 of 2014 concerning Government Administration, Law No. 10 of 2016 concerning Regional Elections, and court decisions as primary legal materials. The results of the study show that the defendant, an active Public Official, was proven to have transferred the functions of state positions, government programs, and facilities for electoral purposes by making political statements in official activities. The judge assessed the formal and material elements in a balanced manner, so that the act was categorized as an abuse of authority as well as an election crime. In conclusion, this ruling sets an important precedent for maintaining the integrity of local democracy by affirming the accountability and neutrality of public officials.